Who borrows?: an analysis of gender, debt and assets in Ecuador, Ghana and Karnataka, India - Grown, Caren (2015)
While there is a substantial and growing literature on household finance in developing countries, less is known about the borrowing behaviour of individual women and men within households: how much they borrow and for what purpose (e.g., to invest in an asset or pay for an expense), where they borrow from, decisions about taking and using credit, and the correlates of individual debt and particular types of debt (e.g., asset debt). This report addresses these questions in Ecuador, Ghana and Karnataka, India using innovative national/state level data sets collected by the Gender Asset Gap project in 2010.